Optimization of Nanosilver Synthesis Process with Bioreductor of Binahong Leaf Extract (Anredera cordifolia (Ten.) Steenis) - Rini Dwiastuti; Elsa Irnandari; Michael Raharja Gani; Sri Hartati Yuliani; Christofori Maria Ratna Rini Nastiti (Sanata Dharma University, 2022)
Nanosilver is a type of metallic silver nanoparticles and has a particle size of 1-100 nm. The method used in the synthesis of nanosilver is a chemical reduction method with silver metal precursor AgNO3 and a bioreductant of binahong leaf extract containing flavonoid compounds. This study aims to obtain the duration, temperature and optimum point in the synthesis of nanosilver with the bioreductant of binahong leaf extract using the sonication method. This type of research is purely experimental with a 2x2 factorial design. The nanosilver characterization was conducted by determining the optimum wavelength and the transmittance value of the nanosilver formed. The effect of temperature and duration of sonication on the wavelength and % transmittance of the synthesized nanosilver in this study were analyzed by ANOVA statistical test using the Minitab 19 application with a 95% confidence level. In this study, the temperature and duration of sonication as well as their interactions have an effect on the transmittance response. The statistical results of the model have a significant effect on the % transmittance response only with p-value 0.05. The optimum point was found in the synthesis of nanosilver with the bioreductant of binahong leaf extract (Anredera cordifolia (Ten.) Steenis) using a 2x2 factorial design, namely at a sonication temperature of 80°C for 10 minutes, a sonication temperature of 70oC for 15 minutes and a sonication temperature of 80oC for 15 minutes.